2013
DOI: 10.1017/dmp.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of Homemade Masks: Would They Protect in an Influenza Pandemic?

Abstract: Our findings suggest that a homemade mask should only be considered as a last resort to prevent droplet transmission from infected individuals, but it would be better than no protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
724
2
47

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(785 citation statements)
references
References 14 publications
12
724
2
47
Order By: Relevance
“…Our theoretical results still must be interpreted with caution, owing to a combination of potential high rates of noncompliance with mask use in the community, uncertainty with respect to the intrinsic effectiveness of (especially homemade) masks at blocking respiratory droplets and/or aerosols, and even surprising amounts of uncertainty regarding the basic mechanisms for respiratory infection transmission [4,41]. Several lines of evidence support the notion that masks can interfere with respiratory virus transmission, including clinical trials in healthcare workers [3,4], experimental studies as reviewed [12,10,9,15,11], and case control data from the 2003 SARS epidemic [1,2]. Given the demonstrated efficacy of medical masks in healthcare workers [3], and their likely superiority over cloth masks in [5], it is clearly essential that healthcare works be prioritized when it comes to the most effective medical mask supply.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our theoretical results still must be interpreted with caution, owing to a combination of potential high rates of noncompliance with mask use in the community, uncertainty with respect to the intrinsic effectiveness of (especially homemade) masks at blocking respiratory droplets and/or aerosols, and even surprising amounts of uncertainty regarding the basic mechanisms for respiratory infection transmission [4,41]. Several lines of evidence support the notion that masks can interfere with respiratory virus transmission, including clinical trials in healthcare workers [3,4], experimental studies as reviewed [12,10,9,15,11], and case control data from the 2003 SARS epidemic [1,2]. Given the demonstrated efficacy of medical masks in healthcare workers [3], and their likely superiority over cloth masks in [5], it is clearly essential that healthcare works be prioritized when it comes to the most effective medical mask supply.…”
Section: Resultsmentioning
confidence: 99%
“…The fit factor for homemade masks averaged 2 in [9], while the fit factor averaged 5 for surgical masks. When volunteers coughed into a mask, depending upon sampling method, the number of colony-forming units resulting varied from 17% to 50% for homemade masks and 0-30% for surgical masks, relative to no mask [9].…”
Section: Mask Efficiency Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies et al. () further compared the surgical and homemade mask and found that the surgical mask was three times more effective in blocking transmission than the homemade mask. Furthermore, the fit performance of a mask can significantly affect the effectiveness of removing exhaled particles (Mansour and Smaldone, ).…”
Section: Introductionmentioning
confidence: 99%
“…First worn by surgical teams a hundred years ago to prevent bacterial contamination of patient's open wounds, early surgical masks were constructed from layers of cellulose materials, more particularly cotton cellulose (gauze) (Haller and Colwell 1918) and derivatives (Arnold 1938) (see also Belkin 1997). Much more recently, face masks made from cotton fabrics have been tested as alternative respiratory protective equipment against pandemic outbreaks such as influenza (Dato et al 2006;Davies et al 2013;Rengasamy et al 2010). Like respirators, current commercially available surgical face masks include several layers of non-woven fabrics with, frequently, a cellulose inner layer in contact with the wearer's face to improve wearer's comfort.…”
Section: Protection Against Airborne Virusesmentioning
confidence: 99%